Five-year Follow-up of Trial of Replication-competent Adenovirus-mediated Suicide Gene Therapy for Treatment of Prostate Cancer - Freytag, Svend O; Stricker, Hans; Peabody, James; Pegg, Jan; Paielli, Dell; Movsas, Benjamin; Barton, Kenneth N; Brown, Stephen L; Lu, Mei; Kim, Jae Ho (Molecular therapy, 2007)
Replication-competent adenovirus-mediated suicide gene therapy is an investigational cancer treatment that combines the oncolytic actions of human adenoviruses with the cytotoxic effects of chemo-radiosensitizing genes. Previously, we reported the short-term effects of this therapy in men with local recurrence of prostate cancer after definitive radiotherapy. With a median prostate-specific antigen (PSA) follow-up of 5 years, we report here the effect of the gene therapy on prostate-specific antigen doubling time (PSADT), a surrogate end point with significant prognostic power. When considering all evaluable subjects, the PSADT increased following the gene therapy from a mean of 17 to 31 months (median 16 to 22 months) (P=0.014). Assuming that salvage androgen suppression therapy androgen suppression therapy (AST) was uniformly initiated at a PSA of 15 ng/mL, the gene therapy would have delayed the projected onset of salvage therapy by an average of 2 years. The results indicate that replication-competent adenovirus-mediated suicide gene therapy may provide a potential long-term benefit to patients, as shown by a lengthening of the PSADT, and delay in when salvage therapy is indicated. Given the high morbidity associated with AST, we believe this approach could provide an attractive treatment option for selection of patients experiencing PSA relapse following definitive therapy.